Resilience And Job Satisfaction Among Paramedics in The Saudi Red Crescent Authority: A Cross-Sectional Study - Saeed Abdulrahman Saeed Alhamdani, Mohammed Matar Meshal Alosaimi, Obaid Meshal Matar Alotaibi, Nabeel Jalal Hshem Zamzami, Abdaldaim Ibrahim Ahmmad Alqasmi, Moneer Abdulaziz Harun Alhosawi; Yahia Sharafi Ahmmad Aseeri, Homood Saad Saleh ALmatrafi, Nawaf Moeen Shalah Alotaibi, Marwan Omarallan Kafyah, Saleh Abdullah Saleh Alzahrani, Abdulqader Waleed Abdugadr Dawaji, Abdullh Hamed Shati Alanazi (Journal of International Crisis and Risk Communication Research, 2024)
Both resistance and job satisfaction of paramedics are necessary factors in ensuring healthy and effective employees. Therefore, the purpose of this cross-sectional study was to examine the relationship between paramedics’ resilience with their job satisfaction and identify the demographic predictors of these variables among paramedics working at the Saudi Red Crescent Authority. Questionnaires included demographics, resilience (Connor and Davidson Resilience Scale), and job satisfaction (Minnesota Satisfaction Questionnaire) were filled by the 300 participating paramedics. The mean resilience score was 58.14 ± 4.66 representing moderate level of resilience. The average mean job satisfaction score was 39.38 ± 3.85 The percentage of low and moderate job satisfaction paramedics were 40.3% and 59.7 %. Pearson correlation analysis also showed that resilience has a positive correlation with job satisfaction with a coefficient value of 0,20 and p < 0,01. In addition, there was no a significant relationship between age, marital status and resilience, and job satisfaction. The results of multiple regression analysis also established job satisfaction as a significant predictor of resilience, accounting for 4% of the variance in resilience, (t = 2.69, p < 0.05). The results indicate that better level of resilience is related to higher levels of job satisfaction of paramedics. The unit reflected that conducting stress and resilience training, creating supportive workplace cultures might improve paramedics’ quality of life and job satisfaction ultimately enhancing patient outcomes. More large-scale research is required to investigate the efficacy of activities for enhancing resilience and job satisfaction among workers in this study.